FIND THE ANSWERS

Prove csc(-x)-sin(-x)=-cosxcotx?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • Prove csc(-x)-sin(-x)=-cosxcotx?


Answers

Find right answers right now! Prove csc(-x)-sin(-x)=-cosxcotx? More questions about Science & Mathematics
Read more
Positive: 34 %
As the title says, Prove: (cosxcotx)/1-sinx - 1 = csc x Any help is appreciated! Thanks.
Read more
Positive: 31 %

More resources

Prove csc(symbol for angle) tan(symbol for angle) = sec(symbol for angle) 2. Prove cosx+sinxtanx=secx November 22, 2010 by Anonymous. Trigonometry
Read more
Positive: 34 %
Prove the identity:cosx/1-tanx+sinx/1-cotx=sinx+cosx 2.Prove the identity: cosx/1+sinx+1+sinx/cosx=2secx August 20, 2011 by Aliya. maths q1) 2cos2x is f(x
Read more
Positive: 29 %
Prove the identity:cosx/1-tanx+sinx/1-cotx=sinx+cosx 2.Prove the identity: cosx/1+sinx+1+sinx/cosx=2secx August 20, 2011 by Aliya. maths q1) 2cos2x is f(x
Read more
Positive: 15 %
... (90 degrees - x) = csc x secx csc-1 = cot^2x Then split sec x and csc-1 into two fractions and multiplied both numerator and denominators by csc and ...
Read more
Positive: 10 %

Show more results